Pengukuran Indeks Kualitas Pengelolaan Pemerintah Provinsi Kepulauan Riau Prespektif Masyarakat Sipil dan Masyarakat Bisnis - Basariah Sitorus (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2013)
This study aims to quantify the quality management of the government's index of Riau Islands province by using the Comparison Method of Exponential (MPE). Respondents were 19 samples consisting of journalists, business people, academic and NGOs, Civil Society research perspective for 5,09 (enough) and the Business Community perspectives of 5,77 (enough). People consider quality management Riau Islands Provincial Government has started to develop good governance with time, effort, budget and resources owned by the public and government.